ความต้องการการพัฒนาทักษะการรู้สารสนเทศสำหรับนักศึกษาปริญญาตรี มหาวิทยาลัยนอร์ท-เชียงใหม่ - พรพนม ประธานราษฎร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purpose of this research was to study the need for developing the Information Literacy Competency Standards for Higher Education among the undergraduate students in North-Chiang Mai University using a sample group of 242 undergraduate students and 92 instructors of the university, a total of 334 subjects. The tool for data collection was a questionnaire based on the Information Literacy Competency Standards for Higher Education of the Association of College and Research Library – ACRL, USA. The statistics for analyzing the data involved frequency, percentage, mean, standard deviation and a t-test. The findings show that students need development in all of the five standards (Standards 1-5) at a high level. Three of the standards that students need development at a high level were Standard Five: The information literate student understands many of the economic, legal, and social issues surrounding the use of information and accesses and uses information ethically and legally; Standard Two: The information literate student accesses needed information effectively and efficiently; and Standard Three: The information literate student evaluates information and its sources critically and incorporates selected information into his or her knowledge base and value system. Regarding the need for teaching and learning management, the three types of courses that were needed at a high level were short courses, stand-alone courses and online courses respectively. The statistical analysis by t-test showed that students wanted development in all five of the standards (1-5) of the Information Literacy Standards. Their need for teaching and learning management was not statistically different at the 0.05 level.